IMPLEMENTASI KONTRAK BELAJAR DIDALAM PERKULIAHAN MENJADI PENDIDIKAN MORAL DI PERGURUAN TINGGI - Husnani Husnani; Sunarti Sunarti (STAI Ma'had Aly Al-Hikam Malang, 2022)
Abstract. Education is not only focused on intellectual ability alone but also must be accompanied by good moral values. Moral education is very important given to students or students as the nation's successor. Teachers and lecturers are educators who are very responsible for providing moral education to students or students, both directly and indirectly. One way that can we use as a media of moral education at higher education or campus is through the application of learning contracts or lecture contracts. Lecturers and college students make an agreement that they will run together for one semester. The implementation of this lecture contract will get maximum results if it starts with a good planning, implementation and evaluation.